PENYELENGGARAAN DESA WISATA DI KABUPATEN LEBAK - Tyas Windu Manisa (Jurnal Penelitian Administrasi Publik, 2020)
The implementation of a tourism village in Lebak Regency is needed to support local potential in order to provide strategic value and broad economic effects. However, in reality there is no policy preparation available to equalize the perceptions of stakeholders in empowering the community through the implementation of a tourism village; This study aims to review the plan for organizing a tourist village and formulate a model for the implementation of a tourist village. The research in this paper was carried out in Lebak Regency. Data collection was carried out through literature studies, in- depth interviews and non-participant observation. The analytical method used is descriptive analysis. This paper shows that the Regency of Lebak needs guidelines for the administration of a tourism village. Keywords: Tourism Village, Guidelines, Sustainable Tourism